Catalyst Deactivation Simulation Through Carbon Deposition in Carbon Dioxide Reforming over Ni/CaO-Al2O3 Catalyst - Istadi Istadi; Didi D. Anggoro; Nor Aishah Saidina Amin; Dorothy Hoo Wei Ling (Bulletin of Chemical Reaction Engineering & Catalysis, 2011)
Major problem in CO2 reforming of methane (CORM) process is coke formation which is a carbonaceous residue that can physically cover active sites of a catalyst surface and leads to catalyst deactivation. A key to develop a more coke-resistant catalyst lies in a better understanding of the methane reforming mechanism at a molecular level. Therefore, this paper is aimed to simulate a micro-kinetic approach in order to calculate coking rate in CORM reaction. Rates of encapsulating and filamentous carbon formation are also included. The simulation results show that the studied catalyst has a high activity, and the rate of carbon formation is relatively low. This micro-kinetic modeling approach can be used as a tool to better understand the catalyst deactivation phenomena in reaction via carbon deposition. © 2011 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)